Factor Influencing Access to Debt Financing in the Business Sector - Gautam, Ramesh Prasad (Journal of Entrepreneurship & Management Studies, 2024)
This study used descriptive research design and data have been collected by survey method from the study area. All the customers of different banks situated in Birendranagar Surkhet were taken as the population of the study. Among the total population, only 180 customers of commercial banks have been selected by using the convenience sampling method. The questionnaire was a tool for data collection. Regression analysis was used to measure the factors influencing access to debt financing in the business sector. Findings indicate that financial information, experience, collateral requirements, and managerial competence have a significant positive impact on debt financing in the business sector in Birendranagar Surkhet.